What price dissection? Dissection literally dissected. Issue 1 (1st June 2001) - Francis, Nathan R; Lewis, Wayne
Abstract : Hamlet: Has this fellow no feelings of his business, that he sings at grave-making? Horatio: Custom hath made it in him a property of easiness. (Hamlet Act V, scene i) 1 Hamlet is appalled by the gravedigger's insensitivity towards death and corpses. Horatio explains that the gravedigger is so accustomed to such things that he no longer shares Hamlet's seriousness. We contend that human dissection may make in medical students and doctors the "property of easiness" in dealing with death and the human body, and that this may have negative consequences for medics and patients. It is perhaps worth emphasising at the outset what this essay is NOT about. We do not wish to call into question the value of dissection in medical education; to charge dissection with being an inefficient or ineffective means of teaching and learning human anatomy is not our intent. Instead, we explore, through the medium of literature, experiences of dissection, and what kind of student and doctor may be encouraged or produced by the dissection room; what price might be paid for a practical, first-hand experience of human anatomy.